(3GdaJhMGJ GdEdgjI aj TQM GdeHGMK GdCUdjIs - (3CHh GdYHGS CMeO Hf eMeO Hf GdegOj Hf YLjHI GdMSfj, GHf YLjHI,J (B1224 (3g` s
(3ChdgG (B:s
(3hSejJg GdaJhMGJ GdEdgjI ai TQM GdeHGMK GdCUdjI s
(3BNQgG (B:s
(3GfJgi cJGH GdaJhMGJ GdEdgjI ai TQM GdeHGMK GdCUdjI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B245s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(113 D) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs